Seeing complexity in public education problems, possibilities, and success for all - Peurach, Donald J., 1962- (New York ; Oxford : Oxford University Press, 2011)
In a period of unprecedented pressure to reform education in the United States, two questions stand out: What is involved in the work of transforming underperforming schools into higher performing schools? And what makes this work so difficult? 'Seeing Complexity in Public Education' examines these questions in light of the history of the Success for All Foundation, an organization that has collaborated with thousands of elementary schools across the US to enact a common design for comprehensive school reform.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public schools -- United States; School improvement programs -- United States